A randomized, open‐label 3‐way crossover study to investigate the relative bioavailability and bioequivalence of crushed sildenafil 20 mg tablets mixed with apple sauce, extemporaneously prepared suspension (EP), and intact sildenafil 20 mg tablets in healthy volunteers under fasting conditions. Issue 1 (30th October 2014) - Gao, Xiang; Ndongo, Marie‐Noella; Checchio, Tina M.; Cook, Jack; Duncan, Barbara; LaBadie, Robert R.
Abstract The relative bioavailability and bioequivalence of 20‐mg doses of a pediatric formulation of sildenafil extemporaneous preparation suspension (EP; 10 mg/mL), the sildenafil 20‐mg intact tablet and the crushed sildenafil 20‐mg tablet mixed with apple sauce were assessed in a single‐dose, randomized, open‐label, 3‐way crossover study with 18 healthy adult volunteers. Blood samples were collected at predefined times and analyzed for sildenafil plasma concentrations. Natural log‐transformed sildenafil pharmacokinetic parameters (Cmax, AUClast, and AUCinf) were used to estimate relative bioavailability and construct 90% confidence intervals (CI) using a mixed‐effects model. Bioequivalence was concluded among the three formulations with one exception, in which the EP suspension showed a 15% decrease in Cmax with a lower 90% CI of 76% compared with the intact tablet. The 15% decrease in sildenafil Cmax is not considered to be clinically relevant. Therefore, the EP suspension is considered to be an appropriate pediatric formulation. All 3 formulations were well tolerated in healthy adult volunteers.